The Analysis of Wadiah Contract in Sharia Savings Products According to Islamic Economic Law - Beri Tantoni; Evita Sri Hidayanti; Sri Setianingsih; Zaitun Qamariah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to analyze wadiah contracts in sharia savings products based on the perspective of Islamic economic law. The method used in this research is a literature review, where data is collected from various relevant literature, including scientific journals, textbooks and official documents. This research examines the basic concepts and principles of wadiah contracts, as well as their application in sharia savings products in various financial institutions. In addition, this research also evaluates the suitability of wadiah contracts with the principles of Islamic economic law regulated by the National Sharia Council-Indonesian Scholars Council (DSN-MUI). The analysis results show that wadiah contracts, when implemented correctly, are in line with sharia principles, provide benefits to customers and financial institutions, and increase trust and participation in the sharia banking system. However, there are several implementation challenges that need to be overcome to ensure full compliance with sharia. This research is expected to provide insight for practitioners and academics in understanding and implementing wadiah contracts in sharia savings products.